2023
DOI: 10.1097/rct.0000000000001460
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Deep-Learning Image Reconstruction With Hybrid Iterative Reconstruction for Evaluating Lung Nodules With High-Resolution Computed Tomography

Abstract: ObjectiveThis study aimed to investigate the impact of deep-learning reconstruction (DLR) on the detailed evaluation of solitary lung nodule using high-resolution computed tomography (HRCT) compared with hybrid iterative reconstruction (hybrid IR).MethodsThis retrospective study was approved by our institutional review board and included 68 consecutive patients (mean ± SD age, 70.1 ± 12.0 years; 37 men and 31 women) who underwent computed tomography between November 2021 and February 2022. High-resolution comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…One reason for the improved depiction of temporal bone structures with DLR is likely related to reduced image noise. Several studies of DLR reconstruction in other body regions have found that image noise is significantly reduced in DLR images compared with HIR images [ 9 – 11 , 19 25 ]. Our study, which assessed image noise in the temporal bone region, accords with those earlier studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One reason for the improved depiction of temporal bone structures with DLR is likely related to reduced image noise. Several studies of DLR reconstruction in other body regions have found that image noise is significantly reduced in DLR images compared with HIR images [ 9 – 11 , 19 25 ]. Our study, which assessed image noise in the temporal bone region, accords with those earlier studies.…”
Section: Discussionmentioning
confidence: 99%
“…Full iterative reconstruction reduced image noise considerably and improved the quality of CT images [ 3 8 ]; however, the associated prolonged image reconstruction time hampered the use of this algorithm in daily clinical practice. An alternative hybrid iterative reconstruction (HIR) algorithm that provides some reduction in image noise within a clinically feasible reconstruction time was subsequently widely accepted [ 9 – 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To our best knowledge, no study has evaluated whether DLR could reduce artifacts caused by arms positioned alongside the torso. As there has been a previous report that artifacts of the lung could be reduced with DLR, 14 we hypothesized that armrelated artefacts could also be reduced with DLR.…”
Section: Introductionmentioning
confidence: 96%
“…It was trained with paired data, one with low noise and high spatial resolution and another with noise contamination and learned the difference between noise and signal. 17,18 It has been reported that the appropriate algorithm of DLR can improve image quality of CT images in various body regions [19][20][21][22][23][24] including the lung, 25 we hypothesized that this reconstruction algorithm could also potentially improve the interobserver agreement in the evaluation of honeycombing in patients with ILD.…”
Section: Introductionmentioning
confidence: 99%